UJI PENGGUNAAN SLUDGE LIMBAH KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) PADA MEDIUM SUBSOIL DYSTRUDEPTS - Sidabutar, Pradianto; Khoiri, M. Amrul; ', Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to determine the effect of sludge palm oil waste on the growth of cocoa seedling (Theobroma cacao L.) on medium subsoil Dystrudepts and get the best dose. This research was conducted in October 2014 until January 2015 in the experimental station on the Faculty of Agriculture, University of Riau, Bina Widya Campus Km 12.5 Simpang Baru Village, Tampan District, Pekanbaru. This research was conducted by using a completely randomized design (CRD) with 6 treatments and 3 replications. The treatments sludge palm oil waste are: S0 = 0 g/polybag, S1 = 50 g/polybag, S2 = 100 g/polybag, S3 = 150 g/polybag, S4 = 200 g/polybag and S5 = 250 g/polybag. Parameters measured were seedling height, stum circle, number of leaves, leaf area widest, root volume, the shoot root ratio and seedling dry weight. The results of research that using of sludge palm oil waste dose of 200 g/polybag to 250 g/polybag on medium subsoil Dystrudepts showed growth of cocoa seedling is best that indicated of increase the seedling height, stum circle, number of leaves, leaf area widest, root volume, the shoot root ratio and seedling dry weight. Keywords: Cocoa seedling, sludge palm oil waste, medium subsoil.